Characterization of the surface redox process of adsorbed morin at glassy carbon electrodes - Tesio, Alvaro Yamil (2011)
The thermodynamic and kinetics of the adsorption of morin (MOR) on glassy carbon (GC) electrodes in 0.2 moldm−3 phosphate buffer solutions (PBS, pH 7.00) was studied by both cyclic (CV) and square wave (SWV) voltammetries. The Frumkin adsorption isotherm was the best to describe the specific interaction of MOR with GC electrodes. The SWV allowed to characterize the thermodynamic and kinetics of surface quasi-reversible redox couple of MOR, using the combination of the ?quasi-reversible maximum? and the ?splitting of SW net peaks? methods. Average values obtained for the formal potential and the anodic transfer coefficient were (0.27±0.02)V and (0.59±0.09), respectively. Moreover, a value of formal rate constant (ks) of 87s−1 for the overall two-electron redox process was calculated. The SWV was also employed to generate calibration curves, which were linear in the range MOR bulk concentration (c∗ MOR) from 1.27×10−7 to 2.50×10−5 moldm−3. The lowest concentration experimentally measured for a signal to noise ratio of 3:1 was 1.25×10−8 moldm−3 (3 ppb).